Management of severe acute encephalopathy in the ICU: an expert consensus statement from the french society of intensive care medicine - Sonneville, Romain; Azabou, Eric; Bailly, Pierre; Benghanem, Sarah; De Almeida Cardoso, Gilles; Claquin, Pierre; Cortier, David; Gaudemer, Augustin; Hermann, Bertrand; Jaquet, Pierre; Lambrecq, Virginie; Legouy, Camille; et al. (Annals of intensive care, 2025)
Introduction Acute encephalopathy in the ICU poses significant diagnostic, therapeutic, and prognostic challenges. Standardized expert guidelines on acute encephalopathy are needed to improve diagnostic methods, therapeutic decisions, and prognostication. Methods The experts conducted a review of the literature, analysed it according to the GRADE (Grading of Recommendation, Assessment, Development and Evaluation) methodology and made proposals for guidelines, which were rated by other experts. Only expert opinions with strong agreement were selected. Results The synthesis of expert work and the application of the GRADE method resulted in 39 recommendations. Among the 39 formalized recommendations, 1 had a high level of evidence (GRADE 1 +) and 10 had a low level of evidence (GRADE 2 + or 2-). These recommendations describe indication for ICU admission, use of clinical scores and EEG for diagnosis, detection of complications, and prognostication. The remaining 28 recommendations were based on expert consensus. These recomandations describe common indications for blood and CSF studies, neuroimaging, use of neuromonitoring, and provide guidelines for management in the acute phase. Conclusion This expert consensus statement aims to provide a structured framework to enhance the consistency and quality of care for ICU patients presenting with acute encephalopathy. By integrating high-quality evidence with expert opinion, it offers a pragmatic approach to addressing the complex nature of acute encephalopathy in the ICU, promoting best practices in patient care and facilitating future research in the field.